Nutrient status of soils in the rain forest of Mt. Pangasugan, Leyte, Philippines - Zikeli, Sabine; Asio, Victor B.; Jahn, Reinhold (Annals of Tropical Research, 2000)
Soils under rain forests are until now poorly understood. This study was conducted to determine if nutrient status is a limiting factor in the rain forest soils of Mt. Pangasugan in Leyte, Philippines. Four sampling sites at varying elevations in a representative catena were studied. In each site, three soil profiles representing the upper, middle and lower slopes were sampled. Soil samples were analyzed for OM, N, P, K, Ca and Mg. Results showed that, except phosphorus, the nutrients are not limiting in the rain forest soils studied. Phosphorus appears limiting despite the fact that some amount of it is brought into the ecosystem by rain. Results also showed a generally high spatial variability of the nutrient status of the soils in the study site.